The Why’s, What’s, and How’s of Timed Artificial Insemination Programs - J. Stevenson; L. Mendonca (Kansas Agricultural Experiment Station Research Reports, 2015)
This report summarizes the benefits of using timed artificial insemination (AI) programs in lactating dairy cows. Since its beginnings, use of Ovsynch has penetrated the dairy industry and is most prevalent in the Midwest and Northeast regions of the U.S. The timed AI program benefits farms that have difficulties with heat detection. Heat detection challenges can occur because of inadequate observation or poor expression of heat associated with footing conditions. Explanation of mechanisms associated with hormone injections are presented to justify the success of currently recommended timed AI programs.
Keywords: timed AI; mechanisms; Ovsynch